2010
DOI: 10.1097/fpc.0b013e328338ac8c
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of levamisole receptor subunits in parasitic nematode species and abbreviated transcripts associated with resistance

Abstract: The candidate gene strategy developed in this study revealed an unexpectedly high diversity of L-AChR subunits specific to the trichostrongylid parasites that are a principal target for the drug LEV. Abbreviated variants, predicted to produce nonfunctional unc-63, were associated with LEV resistance. This study contributes significantly to a better understanding of LEV receptor constitution in parasitic nematodes and highlights the putative role of aberrant mRNA encoding L-AChR subunits in LEV resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 46 publications
7
88
0
3
Order By: Relevance
“…It is noteworthy that the LEV-8 subunit has not been detected in Trichostrongylid parasites, and ACR-8 is the candidate to replace it in L-AChRs Neveu et al, 2010). Because this receptor constitutes the target of levamisole, ACR-8 may be involved in the molecular mechanisms leading to levamisole-resistance acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the LEV-8 subunit has not been detected in Trichostrongylid parasites, and ACR-8 is the candidate to replace it in L-AChRs Neveu et al, 2010). Because this receptor constitutes the target of levamisole, ACR-8 may be involved in the molecular mechanisms leading to levamisole-resistance acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Nematode parasites cause substantial mortality and morbidity in the human population and losses in livestock and domestic animals. The free-living nematode C. elegans is a valuable tool for the study of anthelmintic targets because it shares physiological and pharmacological characteristics with parasitic nematodes, and it is sensitive to most anthelmintic drugs (Jones et al, 2005;Neveu et al, 2010). C. elegans has also emerged as a useful model organism for studying human neuromuscular diseases and for drug testing (Jones et al, 2005(Jones et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…levamisole, pyrantel) resistance are very encouraging (Snabel et al, 2000;Martin and Robertson, 2007;Neveu et al, 2007Neveu et al, , 2010Fauvin et al, 2010). Some progress has been made toward identifying markers for macrocyclic lactone resistance (Njue and Prichard, 2004;Prichard and Roulet, 2007;De Mottier and Prichard, 2008;Beech et al, 2010), but the phenomenon appears to be complex, and perhaps to vary between species.…”
Section: Strongylid Nematodes and Trichurismentioning
confidence: 94%
“…Further research showed that resistance to levamisole is associated with a spliced variant of the acr-8 gene, referred to as Hco-acr-8b which showed elevated expression in resistant worms and was undetectable in susceptible worms (Williamson et al, 2011). Neveu et al (2010) reported the presence of four paralogues of the gene . These observations suggest that the LEV receptor of some parasitic nematodes may not be the same as those found in C.…”
Section: Specific Mechanisms Of Anthelmintic Resistancementioning
confidence: 99%
“…Studies conducted on the pig nematode, Oesophagostomum dentatum, involving different members of this class including levamisole and pyrantel showed that there was a lower percentage of opened ionchannels in resistant worms compared to the counterparts, suggesting an increased desensitization of drug receptors in resistant isolates (Robertson et al, 1999(Robertson et al, , 2000. Neveu et al (2010) (Boulin et al, 2011). Further research showed that resistance to levamisole is associated with a spliced variant of the acr-8 gene, referred to as Hco-acr-8b which showed elevated expression in resistant worms and was undetectable in susceptible worms (Williamson et al, 2011).…”
Section: Specific Mechanisms Of Anthelmintic Resistancementioning
confidence: 99%